Effectiveness of imochem (augmented reality mobile application for organic chemical mechanisms): a preliminary study - Nurul Najidah Mohamed,; Salmiah Jamal Mat Rosid,; Ismahafezi Ismail,; Norsyafikah Asyilla Nordin,; Nurulhuda Mohammad Yusoff,; Siti Noor Syuhada Mohd Amin,; Sarina Mat Rosid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Organic chemistry is considered a complicated science subject in chemistry, especially when it involves the mechanism. The importance of this topic in the foundation study is to understand the basics of reaction and how chemical reactions react through mechanism. It has long been a belief in science education that the laboratory has the potential to be a place where theory and practice can coalesce for students. However, from the previous observation during the class, it was found that most foundation students can not relate the theory they learned during the lecture to the laboratory experiment. Therefore, this study aims to develop an inquiry based Augmented Reality (AR) learning tool for foundation chemistry courses, examine its effect on students’ cognitive performance, compare its effects on high-achieving and low achieving students, and investigate students’ attitudes toward the software. The effectiveness of this AR mobile apps was investigated using question and the students need to answer that question before and after the use of AR mobile apps. A qualitative data was collected among he students after the completion of use AR mobile apps using questionnaire. A statistical analysis has been done using paired t-test and it shows that the t-test yielded a Pearson correlation of -0.15 with variances of 17.24 and 3.67 for low achievers and high achievers, respectively. Therefore, this study is anticipated to reinforce students' knowledge, facilitate better learning, and improve test scores in organic chemistry courses, particularly in the mechanism section.